Optimal transfer pricing under postcontract information* - BANKER, RAJIV D.; DATAR, SRIKANT M. (Contemporary Accounting Research, 1992)
Abstract. This paper analyzes a formal principal‐agents model of resource allocation and coordination in which demand for transfer pricing arises endogenously within a decentralized environment characterized by asymmetric information and divergence of preferences. It is shown that a modified Groves scheme achieves full information efficiency in a setting of the type considered by Harris, Kriebel, and Raviv (1982) and Cohen and Loeb (1984) only if the information asymmetry is postcontract and collusion is precluded. Conditions for the optimality of a coordination mechanism that is immune to collusion are also examined. It is shown that demand for a collusion‐free marginal cost‐type transfer pricing scheme arises if the agents are risk neutral, the cost function is separable but not necessarily linear, and the information asymmetry is postcontract. Résumé. Les auteurs analysent un modèle structuré d'affectation des ressources et de coordination mandant‐mandataire, dans lequel la demande de prix de cession interne est issue, de façon endogène, d'un contexte décentralisé caractérisé par une information asymétrique et une divergence des préférences. Les auteurs démontrent qu'un schéma Groves modifié permet d'atteindre l'efficacité maximum de l'information dans un contexte semblable à celui qu'utilisent Harris, Kriebel et Raviv (1982) et Cohen et Loeb (1984), uniquement si l'asymétrie de l'information est postérieure au contrat et si la collusion est rendue impossible. Ils examinent également les conditions d'optimalité d'un mécanisme de coordination qui est à l'abri de la collusion. Les auteurs démontrent qu'il y a demande de prix de cession interne, à l'abri de la collusion, du type coût marginal si les mandataires sont neutres à l'egard du risque, si la fonction de coûts peut être isolée sans être nécessairement linéaire, et si l'asymétrie de l'information est postérieure au contrat.